Improving Learning Outcomes of Pancasila Education Using Cooperative Learning in SMPN 4 Students of Probolinggo City - Fahira Cahyadika Lisyanti; Sudirman Sudirman (Global Education Journal, 2026)
Pancasila and Citizenship Education (PPKn) plays an important role in shaping character, understanding of national values, and students' awareness of democracy. However, the learning outcomes of PPKn at SMPN 4 Probolinggo City still show low achievements, with many students not yet reaching the Minimum Completeness Criteria (KKM). This research aims to improve PPKn learning outcomes through the application of the Cooperative Active Learning (CAL) model. The research method uses a descriptive quantitative approach by collecting data through observation, questionnaires, and documentation in grade VIII students. The CAL model emphasizes cooperative learning activities in small groups through group discussions, problem-solving, and evaluations so that students play an active role both cognitively and socially. The results of the data analysis showed that there was an increase in student learning outcomes after the implementation of the CAL model compared to before the implementation, both in terms of material understanding and social skills. In addition, students are more motivated, actively discuss, and able to apply PPKn material in the context of daily life. Thus, the Cooperative Active Learning model has proven to be effective in improving PPKn learning outcomes while fostering collaboration skills, individual responsibility, and active participation of students. This research is expected to be a practical reference for teachers in choosing innovative learning strategies to improve the quality of PPKn education.